Hospitalised cancer patients' perceptions of individualised nursing care in four European countries - Suhonen, Riitta A.; Charalambous, Andreas; Berg, Agneta C.; Katajisto, Jouko K.; Lemonidou, Chryssoula; Patiraki, Elisabeth; Sjövall, Katarina; Stolt, Minna; Radwin, Laurel E. (My University, 2018)
The aim of this study was to describe hospitalised cancer patients' perceptions of individualised care in four European countries and compare these perceptions using the patients' socio-demographic characteristics and the Individualized Care Scale. The patients' socio-demographic characteristics used were: education, age, gender, type of hospital admission, previous hospitalisation and hospital length of stay. The Individualized Care Scale has two parts (1) nurses' support of individuality and (2) patients' receipt of individuality. Data (n = 599) were collected in Cyprus (n = 150), Finland (n = 158), Greece (n = 150) and Sweden (n = 141). Multivariate analysis of variance models were constructed and differences in perceptions of individualised care were analysed using the patients' socio-demographic characteristics as covariates. The level of support for individuality and receipt of individualised care was reported as moderate and good respectively. Generally, the highest assessments were made by the Swedish respondents and the lowest by those in Greece. This study revealed some between-country differences in patients' perceptions of care individualisation. These differences, for example, conceptual, educational, based in clinical practice or in the health organisation, require further research. Enquiry into the individualised care perceptions of health care providers and the families of cancer patients would also be useful.
Keywords: Cross-country comparison; Individuality; International; Nursing; Patient; Survey